Uji Organoleptik Eco-Enzyme dari Limbah Kulit Buah - Rivo Yulse Viza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the characteristics of eco-enzyme products from fruit peel waste. The method used is an experiment with a qualitative approach. The results showed that the eco enzyme product produced had a fresh sour aroma, brown with different levels of color density, ranging from light brown, yellowish-brown, to dark brown. The volume of eco enzyme products after the fermentation process for three months showed that in variables 1 and 3 the volume increased to 133%, while in variable 3 there was a reduction in product volume to 86%. The highest pH level is in variable 4 (2.8). In conclusion, the combination of fruit peel waste used as raw material for making eco enzymes affects the color, aroma, water content and pH of the resulting eco-enzymes. Keywords: Eco enzyme, Fruit Peel Waste, Organoleptic